Mediating effects of social detachment in young and middle-aged stroke patients between stigma and ability to return to work - Dong, Jinping; Ding, Xueying; Wen, Yating; Sun, Shujie; Wu, Jingliang; Wang, Jianhua; Fan, Yang; Hu, Guojing; Xin, Zhang; Li, Jiayin; Sun, Xiaoyan (Frontiers in Public Health, 2025)
ObjectiveTo investigate the mediating effect of social isolation on the relationship between stigma and work ability in young and middle-aged stroke patients.MethodsFrom May 2022 to May 2024, a survey was conducted on young and middle-aged stroke patients visiting the neurology department of a tertiary hospital in Weifang. The survey utilized the General Information Questionnaire, the Rankin Scale, the General Isolation Scale, the Stigma Scale for Stroke Patients, and the Work Ability Scale.ResultsThe scores for work ability, social isolation, and stigma among young and middle-aged stroke patients were 44.23 ± 12.72, 46.27 ± 5.17, and 43.37 ± 4.48, respectively. There was a positive correlation between stigma and social isolation scores (r = 0.550, P < 0.01), and a negative correlation between stigma and work ability scores (r = −0.371, P < 0.01). Social isolation was negatively correlated with work ability (r = −0.418, P < 0.01). Multiple linear stepwise regression analysis indicated that stroke type, duration of illness, mRS score, stigma, and social isolation are significant factors affecting work ability in young and middle-aged stroke patients. Social isolation significantly mediated the relationship between stigma and work ability, accounting for 21.66% of the total effect.ConclusionStigma and social isolation can directly predict the level of work ability in young and middle-aged stroke patients. Additionally, stigma can indirectly influence work ability through social isolation.